Profiling The College Students’ Anxiety in Statistics Lectures - Ahmad Dzulfikar (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2021)
Statistics has been a compulsory subject in many study programs, considering its importance as a provision for university students to conduct research, which is one of the requirements for graduation. However, statistics anxiety, which hurts statistical competence, is a common phenomenon in students. This study, first, aims to describe students' statistics anxiety. It also wants to examine whether gender differences are also a cause of this statistics anxiety. The study took 167 samples of students at a university in Central Java, Indonesia. They were selected by simple random sampling. The statistics anxiety scale has been tested for its validity and reliability and becomes the instrument in this study. This study found that the majority of students' statistics anxiety was on average at a moderate level. It also found no difference in statistics anxiety based on gender, seen either as a whole or in terms of each domain. Further related research is expected to examine statistics anxiety with a qualitative approach or mixed methods to describe its nature and causes in more depth, as well as efforts that can be made to reduce such anxiety. Keywords: statistics anxiety, gender, interpretation